Tinjauan Psikologi terhadap Fenomena Bipolar pada Karakter Akashi Seijuro dalam Anime Kuroko no Basket - Lalu Pradipta Jaya Bahari (HARAPAN: Jurnal Ilmu Kesehatan dan Psikologi, 2025)
This study stems from the growing attention to the representation of mental disorders in popular media and its impact on public understanding. The focus is on the character Akashi Seijuro from Kuroko no Basket, who displays behavioral duality often associated with bipolar phenomena. The main objective is to analyze Akashi’s behavior through the lens of clinical psychology, assess its alignment with bipolar characteristics according to the DSM-5, and examine its implications for mental health literacy. The research adopts a qualitative descriptive-analytical approach using literary psychology methods, supported by narrative analysis of episodes 5–25 from Season-3 of the anime. Findings indicate that Akashi exhibits traits resembling bipolar disorder, such as grandiosity, extreme mood shifts, and emotional withdrawal. However, these patterns primarily represent identity conflict and the pressures of authority rather than clinical symptoms. The depiction is symbolic and serves as a dramatic device to deepen narrative complexity rather than a medical portrayal of mental illness. The study emphasizes the importance of an interdisciplinary approach in bridging clinical psychology and media studies while underscoring the need for media literacy and professional consultation to ensure that portrayals of mental health in popular culture are more empathetic and stigma-free.